Prevalence of sleep – wake cycle disturbance among cancer patients of Bhaktapur cancer hospital, Nepal - Marita, P; Acharya Pandey, R (Journal of Chitwan Medical College, 2017)
Cancer patients are at great risk for developing insomnia and disorders of the sleep-wake cycle. Insomnia is the most common sleep disturbance in this population and is most often secondary to physical and/or psychological factors related to cancer and/or cancer treatment. It is estimated that nearly 45% of cancer patients experience sleep disturbances; this is nearly three times the estimate of its occurrence in the general population. The purpose of the study is to determine the prevalence of sleep-wake cycle disturbance in patient receiving chemotherapy. A descriptive cross-sectional study was carried out in 2013. A total of 205 respondents, visiting Bhaktapur Cancer Hospital and who met criteria were purposively sampled and interviewed face to face. Insomnia Severity Index Scale was used to grade insomnia. Descriptive statistics such as frequency and percentage was used to describe demographic data. Chi-square test was done to find out the association between prevalence of sleep-wake cycle disturbance and selected variables. Among the total respondents (205), 70.7% had sleep-wake cycle disturbances. Majority (71.21%) of respondents had some form of clinically significant insomnia. The ages of the respondents ranged from 20 to 81 years with the mean age of 56.25 (SD ± 13.87). More than half i.e. 69.3% of the respondents were female. Patients being treated with Methotrexate were found to be more associated with the development of sleep-wake cycle disturbance. The significant association was found on drinking tea/coffee with the prevalence sleep-wake cycle disturbance. Sleep disorders are a common and often chronic problem for patients with cancer. Recently, such symptoms have attracted little attention. This might be the reasons for increased prevalence of sleep-wake cycle disturbance. It is recommended to take early and adequate intervention for the reduction of increased prevalence rate of sleep-wake cycle disturbance.